PENGARUH STRATEGI KEUNGGULAN BERSAING DAN ORIENTASI PASAR TERHADAP KINERJA PEMASARAN PERUSAHAAN - Basuki Basuki; Rahmi Widyanti (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2014)
Based on empirical studies and theoretical studies that market orientation and strategic competitive advantage and a good marketing performance can be achieved by Industry Small and Medium Enterprises (SMEs) when they can meet-indigo value of each variable in an integrated manner. Therefore, the relationship of these variables influence is very interesting to do the assessment and tested empirically in the context of the Small Business Industry mengah (SMEs) in South Kalimantan Province. The purpose of this study theoretically (long-term) is expected for the development of the science, especially in the field of marketing management related to market-oriented marketing strategies to achieve competitive advantage in order to improve the performance of SMEs Company marketing. While practical purposes (short-term) is the finding of this study is expected to provide information on the perpetrators indsustri small and medium enterprises (SMEs) as a basis for improving the quality of products and services through the process of market orientation. The method used in this study is a survey method, whereas this type of research is classified as explanatory research. Data analysis tool used in this study is the Partial Least Square (PLS) The studies have shown that the market orientation positive significant effect on the competitive advantage Strategy and Performance pemesaran company. Competitive advantage strategy significantly positive effect on the performance of corporate marketing. Also the orientation of the market through the support of competitive advantage Strategy positive significant effect on the improvement of the company's marketing performance.Keywords: Competitive Advantage Strategy, Market Orientation, and Performance Marketing Company